Spatio-temporal regulation of EGFR signaling by the Eps15 homology domain-containing protein 3 (EHD3) - Amessou, Mohamed (Oncotarget, 2016)
The epidermal growth factor (EGF) receptor EGFR is a major receptor tyrosine kinase whose role in gliomagenesis is well established. We have recently identified EHD3 [Eps15 homology (EH) domain-containing protein 3], an endocytic trafficking regulatory protein, as a putative brain tumor suppressor. Here, we investigate the underlying mechanisms, by establishing a novel mechanistic and functional connection between EHD3 and the EGFR signaling pathway. We show that, in response to stimulation with the EGF ligand, EHD3 accelerates the rate of EGFR degradation by dramatically increasing its ubiquitination. As part of this process, EHD3 also regulates EGFR endosomal trafficking by diverting it away from the recycling route into the degradative pathway. Moreover, we found that upon EGF activation, rather than affecting the total MAPK and AKT downstream signaling, EHD3 decreases endosome-based signaling of these two pathways, thus suggesting the contribution of EHD3 in the spatial regulation of EGFR signaling. This function explains the higher sensitivity of EHD3-expressing cells to the growth-inhibitory effects of EGF. In summary, this is the first report supporting a mechanism of EHD3-mediated tumor suppression that involves the attenuation of endosomal signaling of the EGFR oncogene.